New fibers - Hongu, Tatsuya, 1929- (Woodhead Pub., 1997)
The first edition of New Fibers was enthusiastically received by a worldwide audience and this second edition has provided an opportunity to revise and update its contents and examine new developments since 1990. There have been considerable changes in the nature of the fibers being produced, the production methods and in consumers' values and expectations. Since 1990, the march of high-tech fibers has continued, with an ever increasing sub-division to meet specialised applications, as in high performance, high-function and high-sense fibers. New research and development has produced fibers with high tenacity and modulus to give the super-fibers now used as industrial materials. The more aesthetic and comfortable modern lifestyle has given rise to improved Shin-gosen and it is this springboard that leads on to 'fibers for the next millennium', the subject of a new chapter. Another new chapter examines the resurgence of synthetic cellulosics since 1990, in particular the various solvent-spun fibers of the Lyocell and Tencell families.